Study and Characterization of Fe3O4-PEG Nanoparticles Using The Co-Precipitation Method For The Production of Permanent Magnets - HANDAYANI, FITRI; Rianna, Martha (Talenta Publisher, 2023)
Natural iron sand is one of the natural resources in Indonesia, especially in the Cianjur area, West Java which has been used optimally. This study aims to analyze Fe's content, properties, and grain size found in Cianjur, West Java. The natural iron sand samples were prepared using the calcination method, which was dried at 50Â°C until the samples became powder. Beach sand samples are extracted using a permanent magnet to separate magnetic and non-magnetic materials. Characterization of iron sand using XRD, SEM, VSM, and FTIR. The XRD results show that the natural iron sand sample has a single magnetite phase (Fe3O4). A spinel cubic crystal structure is formed with lattice parameters of 8,513 Çº using Co-Precipitation. SEM results show that the sample is inhomogeneous or homogeneous, as indicated by the gap and agglomeration of particles in each sample. VSM results show that the parameter magnetic properties saturation (Ms) on average is 23.9763735 emu/g, magnetic remanence (Mr) is on average 5.14865198 emu/g, and coercivity is on average 125.139457033 emu/g. Where in sample 1, saturation is 29.7729509 emu/g, remanance is 4.0486018 emu/g, coercivity is 92.1368641 emu/g, sample 2 is saturation 21.5994425 emu/g, remanance 8.18772602 emu/g, coercivity 179.567079 emu/g and sample 3 has a saturation value of 20.55672771 emu/g, remanance 3.20962812 emu/g. Then, the FTIR results showed a shift in the vibration peak, which experienced a change in the vibrational energy of Fe-O and then showed the -OH group at an absorption of 3400/cm. The results of this study have the potential to process other magnetic materials.